The Role of Digital Technology in the Transformation of Agriculture Toward Smart Farming - Rasyid, Harun; Mumpuni Ningsih, Gumoyo (Riviera Publishing, 2024)
Agriculture is one of the important sectors in the Indonesian economy. However, the agricultural sector also faces various challenges, such as climate change, limited land, and high production costs. One solution to overcome these challenges is to utilize digital technology. The transformation of agriculture towards smart farming is one effort to utilize digital technology in agriculture. The aim of this research is to analyze the role of digital technology in the transformation of agriculture towards smart farming. This study used qualitative research methods. The data collection technique in this research is a literature study with publication period criteria in the last 10 years, namely 2014-2024. The data obtained was then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. Research results from 15 pieces of literature show that digital technology plays an important role in the transformation of agriculture towards smart farming. Digital technology can increase agricultural productivity, agricultural operational efficiency and the competitiveness of agricultural products. Digital technology can increase agricultural productivity by increasing the efficiency of agricultural inputs and increasing agricultural productivity. Meanwhile, the company's operational efficiency is through increasing the effectiveness of communication and supply chain management. Meanwhile, product competitiveness is carried out by improving product quality and increasing product added value.